A study on awareness and prevention of dengue fever among outpatients attending a health centre in the rural area of Kancheepuram district - Johnpaul, A.; Thoufiq, A. Abdul Azeez; Umadevi, R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Dengue fever has become one of the major public health problems in all developing countries. It is essential to create awareness among people as it can be prevented by simple practices. The study was conducted to find the awareness among the people thus determining the need to educate the people regarding the preventive measures of dengue fever. Methods: This was a cross-sectional community-based study conducted among the outpatients and their attenders visiting a Rural Health Training Center of private Medical College and Hospital, belonging to Alandur block in Kancheepuram district, Tamil Nadu during January 2019 to March 2019. 260 subjects within the age group of 18 to 82 years were selected by convenient sampling method. The data was collected by interviewing and by using questionnaires. Analysis of the structured data was done using SPSS software version 16. Results: The study included 260 respondents who gave their consent for the study. 60.8% of the study group were males. Mean age of the study group was 35.36 years. 58.1% of the individuals were educated more that 10th standard. Knowledge about the mode of transmission was correctly stated by 85.8%. Around 15% were not aware of breeding places of mosquitoes. Conclusions: From this study it was evident that there is a definite gap in understanding the various aspects of dengue fever. Thus, we conclude that regular awareness programs should be conducted in the form of campaigns and house visits to create awareness among all individuals.